2012
DOI: 10.1371/journal.pone.0031147
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Preprocessing and Analysis Pipelines for Single-Subject fMRI: 2. Interactions with ICA, PCA, Task Contrast and Inter-Subject Heterogeneity

Abstract: A variety of preprocessing techniques are available to correct subject-dependant artifacts in fMRI, caused by head motion and physiological noise. Although it has been established that the chosen preprocessing steps (or “pipeline”) may significantly affect fMRI results, it is not well understood how preprocessing choices interact with other parts of the fMRI experimental design. In this study, we examine how two experimental factors interact with preprocessing: between-subject heterogeneity, and strength of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 57 publications
(99 reference statements)
2
58
0
Order By: Relevance
“…The stability of the peak activations also allows us to identify reliable brain regions from a single split, which is not available to voxel-wise bootstrap estimation. The crossvalidation framework is therefore particularly useful when only limited f MRI data is available, and has been previously used to optimize preprocessing in brief task runs of less than 3 minutes in length (e.g., [18,19]). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The stability of the peak activations also allows us to identify reliable brain regions from a single split, which is not available to voxel-wise bootstrap estimation. The crossvalidation framework is therefore particularly useful when only limited f MRI data is available, and has been previously used to optimize preprocessing in brief task runs of less than 3 minutes in length (e.g., [18,19]). …”
Section: Discussionmentioning
confidence: 99%
“…Control blocks involved touching a fixation cross presented at random intervals of 1-3 s. The resulting 4D f MRI time series were preprocessed using standard tools from the AFNI package, including rigid-body correction of head motion (3dvolreg), physiological noise correction with RETROICOR (3dretroicor), temporal detrending using Legendre polynomials and regressing out estimated rigid-body motion parameters (3dDetrend, see [8] for an overview of preprocessing choices in f MRI). For the majority of results (see Sections 2.2 and 2.3), we preprocessed the data using a framework that optimizes the specific processing steps independently for each subject, as described in [18,19], within the split-half NPAIRS resampling framework [6]. In Section 2.4, we provide more details of pipeline optimization, and demonstrate the importance of optimizing preprocessing steps on an individual subject basis in the PLS framework.…”
Section: Functional Magnetic Resonance Imaging (Fmri) Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…NPAIRS was widely used as the performance metrics in the optimal determination of preprocessing pipelines and dimensionality number, task contrast amplitude impacts investigation and physiological noise suppression, etc. [29][30][32][33][34][35][36][37][38]. The aforementioned researches revealed that enforcing reproducibility of the reproduced SPMs related to brain functional network was quite important in the neuroscience and clinical domain.…”
Section: Spatial Reproducibility Of Spmsmentioning
confidence: 99%